I IMPLEMENTASI PROGRAM WAJIB BELAJAR PENDIDIKAN DASAR 9 TAHUN BAGI SUKU ANAK DALAM - Sofa, Ade; Mawarni, Ega; Maros, Asra'i (STIA Bina Banua Banjarmasin, 2023)
The purpose of this study was to find out about the implementation of the 9-year Compulsory Education Program in Kelukup Hamlet, Dwi Karya Bhakti Village, Pelepat District, Bungo Regency, Jambi. The research method uses a qualitative-descriptive approach. Data collection techniques include observation, interviews, and documentation. The results of the study show that the implementation of the compulsory education program has been carried out quite well but has not yet achieved satisfactory results. Socialization regarding the importance of participating in the program has been conveyed to SAD residents through related parties. Non-governmental organizations play the most crucial role, namely as coaches, supervisors, assistants, and facilitators in every educational activity for the children of the Suku Anak Dalam. There are internal barriers from the SAD community to accepting the program, namely their suspicious attitude, strong customs and traditions, lack of gender equality, shyness and low self-esteem of children, and difficulties in paying for children's school needs. These obstacles were overcome by continuing to provide direction, understanding, and motivation to the SAD community regarding compulsory education, efforts by teachers to visit from door to door to pick up students to study, and efforts to provide scholarships for SAD children in need. Keywords: Implementation, Compulsory Education, Suku Anak Dalam.